Poetry's Afterlife: Verse in the Digital Age - Stein, Kevin (University of Michigan Press, 2011)
At a time when most commentators fixate on American poetry's supposed ""death,"" Kevin Stein's Poetry's Afterlife instead proposes the vitality of its aesthetic hereafter. The essays of Poetry's Afterlife blend memoir, scholarship, and personal essay to survey the current poetry scene, trace how we arrived here, and suggest where poetry is headed in our increasingly digital culture. The result is a book both fetchingly insightful and accessible. Poetry's spirited afterlife has come despite, or perhaps because of, two decades of commentary diagnosing American poetry as moribund if not already deceased. With his 2003 appointment as Illinois Poet Laureate and his forays into public libraries and schools, Stein has discovered that poetry has not given up its literary ghost. For a fated art supposedly pushing up aesthetic daisies, poetry these days is up and about in the streets, schools, and universities, and online in new and compelling digital forms. It flourishes among the people in a lively if curious underground existence largely overlooked by national media. It's this second life, or better, Poetry's Afterlife, that his book examines and celebrates.